Photoproduction of K+K- Pairs in ultraperipheral collisions - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Kroesen, Martin; et al. (Physical review letters, 2024)
𝐾+⁢𝐾− pairs may be produced in photonuclear collisions, either from the decays of photoproduced 𝜙⁡(1020) mesons or directly as nonresonant 𝐾+⁢𝐾− pairs. Measurements of 𝐾+⁢𝐾− photoproduction probe the couplings between the 𝜙⁡(1020) and charged kaons with photons and nuclear targets. The kaon-proton scattering occurs at energies far above those available elsewhere. We present the first measurement of coherent photoproduction of 𝐾+⁢𝐾− pairs on lead ions in ultraperipheral collisions using the ALICE detector, including the first investigation of direct 𝐾+⁢𝐾− production. There is significant 𝐾+⁢𝐾− production at low transverse momentum, consistent with coherent photoproduction on lead targets. In the mass range 1.1<𝑀𝐾⁢𝐾<1.4 GeV/𝑐2 above the 𝜙⁡(1020) resonance, for rapidity |𝑦𝐾⁢𝐾|<0.8 and 𝑝𝑇,𝐾⁢𝐾 <0.1 GeV/𝑐, the measured coherent photoproduction cross section is d⁢𝜎/d⁢𝑦=3.37±0.61⁢(stat)±0.15⁢(syst) mb. The center-of-mass energy per nucleon of the photon-nucleus (Pb) system 𝑊𝛾⁢Pb,𝑛 ranges from 33 to 188 GeV, far higher than previous measurements on heavy-nucleus targets. The cross section is larger than expected for 𝜙⁡(1020) photoproduction alone. The mass spectrum is fit to a cocktail consisting of 𝜙⁡(1020) decays, direct 𝐾+⁢𝐾− photoproduction, and interference between the two. The confidence regions for the amplitude and relative phase angle for direct 𝐾+⁢𝐾− photoproduction are presented.
Im Text sind "+" und "-" hochgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone [und viele weitere]
Gesehen am 21.05.2025